Investigating patients’ experiences with dyspnea associated with warm autoimmune hemolytic anemia (wAIHA) and cognitive debriefing of the FACIT-Dyspnea 10-item short form: a qualitative patient interview study - Michael Kostikas; Rebecca Woodburn; Karen Jones; Quentin Hill; David Kuter; Bruno Fattizzo; Owen Cooper; Marieke Krol; Stephanie Bascle; Laurence Pollissard; Kate Burrows; Ahmed Daak; et al. (Journal of Patient-Reported Outcomes, 2026)
Abstract Background Dyspnea is a prominent symptom in patients with warm autoimmune hemolytic anemia (wAIHA), yet its lived experience remain under-researched. Although clinically relevant, dyspnea is not routinely assessed in wAIHA trials, and no validated patient-reported outcome (PRO) measures exist for this population. This study explored patients’ experience of wAIHA-related dyspnea, identified its most bothersome impacts on daily life, and evaluated the content validity of the FACIT-Dyspnea 10-item Short Form (SF) in wAIHA. Methodology Hybrid concept elicitation and cognitive debriefing interviews were conducted with 15 adults diagnosed with wAIHA in the US. Patients were recruited via recruitment vendors and a patient advocacy group. Interviews were conducted online, transcribed verbatim, and analyzed using inductive and deductive coding. Results All fifteen patients (aged 35–74; 80% female) reported experiencing dyspnea, primarily triggered by physical exertion and alleviated by rest. Twelve (80%) patients reported dyspnea and fatigue exacerbated each other. Most were in remission with three receiving treatment at interview. Thirty-three distinct dyspnea-related impacts were identified, predominantly affecting physical functioning (e.g., difficulty walking) and activities of daily living (ADLs). Emotional (e.g., anxiety) and occupational impacts were also reported. These findings highlight dyspnea’s substantial effect on health-related quality of life (HRQoL).